The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1370/afm.1562
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Long-Term Prognosis of Depression

Abstract: PURPOSE Indicators of prognosis should be considered to fully inform clinical decision making in the treatment of depression. This study examines whether self-rated health predicts long-term depression outcomes in primary care. METHODSOur analysis was based on the first 5 years of a prospective 10-year cohort study underway since January 2005 conducted in 30 randomly selected Australian primary care practices. Participants were 789 adult patients with a history of depressive symptoms. Main outcome measures inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
72
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 49 publications
14
72
0
6
Order By: Relevance
“…Overall, we found strong relationships between all three measures and self-rated health status, which is considered a valid predictor for mortality (DeSalvo et al, 2006), consistent with other studies in primary care settings (Ambresin et al, 2014).…”
Section: Health-related Correlatessupporting
confidence: 90%
“…Overall, we found strong relationships between all three measures and self-rated health status, which is considered a valid predictor for mortality (DeSalvo et al, 2006), consistent with other studies in primary care settings (Ambresin et al, 2014).…”
Section: Health-related Correlatessupporting
confidence: 90%
“…Further, self-rated health has been associated with depression in mixed-age adults (Herrman et al, 2002; Goldney et al, 2010; Gunn et al, 2012). Specifically, one longitudinal study reported that self-rated health predicted recurrence of major depressive disorder up to five years later (Ambresin et al, 2014). However, the direction of the relationship between self-rated health and depression remains uncertain as depression has also been reported to be a risk factor for subsequent decline in self-rated health (Han & Jylha, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, SRH could offer an easy and efficient way to identify patients at risk for poor long-term depression outcomes [2]. According to one previous study from Australia [2], cross-sectional analysis of baseline data showed that participants reporting poor or fair SRH had greater odds of chronic illness, MDD, and lower socioeconomic status than those reporting good to excellent SRH.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, numerous studies suggesting the relation between self-rated health (SRH) and depression have been reported [2, 68]. SRH is able to measure one’s perception of one’s general health status.…”
Section: Introductionmentioning
confidence: 99%